Validasi Program Remaja “STOP” (Sadar, Tolong, dan Perangi) Bullying untuk Mengurangi Intensi Perilaku Bullying pada Siswa SMP - Deni Tri Anggraeni; Amitya Kumara; Muhana Sofiati Utami (Faculty of Psychology, Universitas Gadjah Mada, 2016)
Bullying cases in Indonesia happens among middle school students. Someliteratures mention that bullying behavior in school is supported by peers. This studyaims to validate the program Remaja “STOP” (Sadar, Tolong, dan Perangi) Bullying toprevent and reduce the bullying intention students through peers. Peer facilitators is 19students who never involve bullying behavor, brave to defend and support the victims,have a good communication skills and self confidence. While the subject of this researchis 32 students that getting middle score on Intention Bullying Behavior Scale. Validationtest is used before conducted the research. This study used untreated control groupdesign with pretest and double postest as design experiment. The collected data wasanalyzed with anava mixed design showed that Remaja “STOP” (Sadar, Tolong, danPerangi) Bullying program is valid to improve a fasilitator peer’s antibullyingknowledge and presentation skill. Also, this program is valid tu decrease the intention ofbullying among middle school students.